1999
DOI: 10.1175/1520-0434(1999)014<0289:rrdtpa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Radar Reflectivity–Derived Thunderstorm Parameters Applied to Storm Longevity Forecasting

Abstract: In order for the Federal Aviation Administration (FAA) to use airspace more efficiently during thunderstorm events, accurate storm longevity forecasts are needed. Relationships between 16 radar reflectivity-derived storm characteristics and storm longevity are examined to determine which, if any, of the storm characteristics are strongly related to storm lifetime. Such relationships are potentially useful for the development of storm longevity forecasts. The study includes 879 storms that formed over the Memph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…This result is consistent with MacKeen et al (1999), who find that 16 different parameters did not provide useful information on storm duration. The probabilities of a storm being either isolated rotating or isolated nonrotating, as well as linear or cluster were used as a predictive variable for this test, as well as the upper-level forcing and environmental parameters used in the logistic regression models.…”
Section: Variablesupporting
confidence: 86%
“…This result is consistent with MacKeen et al (1999), who find that 16 different parameters did not provide useful information on storm duration. The probabilities of a storm being either isolated rotating or isolated nonrotating, as well as linear or cluster were used as a predictive variable for this test, as well as the upper-level forcing and environmental parameters used in the logistic regression models.…”
Section: Variablesupporting
confidence: 86%
“…From analysis 1, it was found that the obtained thunderstorm climatology was a very good match with the results obtained by previous researchers for the number of thunderstorm days per year (Alexander 1935;Changnon 1988aChangnon ,b, 2001, the monthly and the diurnal distributions (Wallace 1975;Kelly et al 1985;Easterling and Robinson 1985;Johns and Hirt 1987;Changnon 1988a,b;Bentley and Mote 1998;Klimowski et al 2003), the storm duration (Ackerman and Knox 2006), the storm movement (Bentley and Mote 1998;Johns and Evans 2000;Klimowski et al 2003), the storm-track length (Bentley and Mote 1998), and the storm intensity (MacKeen et al 1999;Johns and Evans 2000).…”
Section: Methods and Validation Of The Usage Of Radar Datasupporting
confidence: 81%
“…Therefore a long lasting thunderstorm produces more rainfall than a shorter one for two reasons: (1) the longest persistence; and (2) the highest average intensity. Despite the fact that it is not possible to forecast the duration of a storm on the only basis of its properties during the first stages of life [18], the results presented in Figure 3 suggest the existence of a relation between the maximum of reflectivity in the first stages of the thunderstorm life cycle and the duration of the entire convective event.…”
Section: The Storm Lifecyclementioning
confidence: 96%
“…The variation of the location of the IDs during the day is hereafter considered. To this end, the day is subdivided in four periods: night (20-04 UTC), morning (04-12 UTC), afternoon (12-15 UTC) and evening (15)(16)(17)(18)(19)(20).…”
Section: The Spatial Distribution Of Ids Over the Regionmentioning
confidence: 99%